Hemlock : a forest giant on the edge - Foster, David R., 1954-; Long, Stephen, 1953-; Baiser, Benjamin H. (Yale University Press, 2014)
The Eastern Hemlock, massive and majestic, has played a unique role in structuring northeastern American forest environments, from Nova Scotia to Wisconsin and through the Appalachian Mountains to North Carolina, Tennessee and Alabama. A 'foundation species' influencing all the species in the ecosystem surroounding it, this iconic North American tree has long inspired poets and artists as well as naturalists and scientists.